Computational Analysis of Biflavonoid Derivatives through Molecular Docking on ALK Kinase Receptor as Potential Inhibitors of A549 Cell Proliferation - Feri Kanti Rahayu; Arinda Nur Cahyani; Syaiful Prayogi; Dossy Susan Anggraeni; Putri Aulia Zahra; Azzahra Rhisma Ernanda; Indah Fajar Falupi; Dila Rahma (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Lung cancer remains one of the leading causes of cancer-related mortality worldwide. In Indonesia, it ranks third after cervical and breast cancers, with non-small-cell lung carcinoma (NSCLC) being the most prevalent type, accounting for 85–88% of cases. Anaplastic lymphoma kinase (ALK) is a key molecular target in NSCLC, contributing significantly to carcinogenesis. However, resistance to current ALK-targeted therapies poses a major challenge. To address this, new drug discovery efforts are urgently needed. While drug development is typically time-consuming and costly, Computer-Aided Drug Design (CADD) offers an efficient strategy at the early stages. Biflavonoid derivatives have shown anticancer potential but are limited by poor solubility and low activity, warranting further optimization. This study explores structural modifications of biflavonoid derivatives to identify potential ALK inhibitors. The results indicate that the modified compounds (Compounds A and B) demonstrated binding affinities comparable to the reference drug, Entrectinib, suggesting their promise as novel anticancer candidates.